The effect of hotel tax and restaurant tax on the original regional revenue of Banjarmasin City - Rukman, Rukman (Institute of Accounting Research and Novation (IARN), 2025)
Hotel tax and restaurant tax are two types of local taxes whose potential continues to grow in line with the increasing attention to supporting components such as the service sector, infrastructure development, and tourism in regional development policies. This study aims to examine the effect of hotel tax and restaurant tax on revenue in Banjarmasin City. This research is quantitative in nature, utilizing time-series data from 2019 to 2023. The data analysis was conducted using multiple linear regression with classical assumption tests. Based on the research findings, the hotel tax variable has a significance value (Sig) of 0.377, which is greater than the alpha value (0.05), indicating that hotel tax (X1) does not have a significant effect on the regional revenue (Y) of Banjarmasin City. Meanwhile, the restaurant tax variable has a significance value (Sig) of 0.000, which is smaller than the alpha value (0.05), indicating that restaurant tax (X2) has a significant effect on the regional revenue (Y) of Banjarmasin City. Furthermore, based on the research results, the p-value is 0.00 < 0.05, which suggests that not all independent variables (hotel tax and restaurant tax) simultaneously influence the dependent variable, which is the regional revenue of Banjarmasin City. The implications of this study encourage the optimization of local tax revenue in Banjarmasin City.